A community‐based continuum of care model for the prevention of postpartum hemorrhage in rural Ghana. Issue 2 (27th November 2012) - Kapungu, Chisina T.; Mensah‐Homiah, Joseph; Akosah, Eric; Asare, Gloria; Carnahan, Leslie; Frimpong, Mavis A.; Mensah‐Bonsu, Paulina; Ohemeng‐Dapaah, Seth; Owusu‐Ansah, Lydia; Geller, Stacie E.
Abstract: Objective: To report on Phase 1 of an operations research study designed to reduce postpartum hemorrhage (PPH)‐related morbidity and mortality in rural Ghana. Methods: Phase 1 of the study—which included a needs assessment, community sensitization, implementation of blood collection drapes, training of service providers, and baseline data collection—comprised preliminary work to prepare for misoprostol distribution in Phase 2. Seventy‐four primary healthcare providers were trained on safe‐motherhood practices, use of blood collection drapes, and data collection. Baseline data were collected from 275 women regarding home deliveries, who attended the deliveries, incidence of PPH, and use of blood collection drapes. Results: Blood collection drapes were used at 67.6% of deliveries, increasing to 88.5% over the final 6 months of Phase 1. Community health extension workers (CHEWs) were present at 57.1% of all deliveries but attendance increased to 86.9% during the last 6 months of Phase 1. Overall, 96.0% of deliveries resulted in healthy outcomes for the mother; 4.0% of births had complications. Conclusion: The preliminary work conducted in Phase 1 of the study was crucial in guiding misoprostol distribution in Phase 2. However, challenges existed, including inadequate community sensitization, low home‐birth attendance by CHEWs, and data collection problems.